High mortality rates in a juvenile free‐ranging marine predator and links to dive and forage ability. Issue 1 (11th December 2019) - Cox, Sam L.; Authier, Matthieu; Orgeret, Florian; Weimerskirch, Henri; Guinet, Christophe
Abstract: High juvenile mortality rates are typical of many long‐lived marine vertebrate predators. Insufficient development in dive and forage ability is considered a key driver of this. However, direct links to survival outcome are sparse, particularly in free‐ranging marine animals that may not return to land. In this study, we conduct exploratory investigations toward early mortality in juvenile southern elephant seals Mirounga leonina . Twenty postweaning pups were equipped with (a) a new‐generation satellite relay data tag, capable of remotely transmitting fine‐scale behavioral movements from accelerometers, and (b) a location transmitting only tag (so that mortality events could be distinguished from device failures). Individuals were followed during their first trip at sea (until mortality or return to land). Two analyses were conducted. First, the behavioral movements and encountered environmental conditions of nonsurviving pups were individually compared to temporally concurrent observations from grouped survivors. Second, common causes of mortality were investigated using Cox's proportional hazard regression and penalized shrinkage techniques. Nine individuals died (two females and seven males) and 11 survived (eight females and three males). All but one individual died before the return phase of their first trip at sea, and all but one were negatively buoyant. Causes of death were variable, although common factors included increased horizontal travel speeds and distances, decreased development in dive and forage ability, and habitat type visited (lower sea surface temperatures and decreased total [eddy] kinetic energy). For long‐lived marine vertebrate predators, such as the southern elephant seal, the first few months of life following independence represent a critical period, when small deviations in behavior from the norm appear sufficient to increase mortality risk. Survival rates may subsequently be particularly vulnerable to changes in climate and environment, which will have concomitant consequences on the demography and dynamics of populations. Abstract : High juvenile mortality rates are typical of many long‐lived marine predators and are likely linked to insufficient development of dive and forage ability. Here, we investigate such processes in juvenile southern elephant seals using a new generation of bio‐logging tags, capable of remotely transmitting behavioral information through the Argos satellite system. We found that causes of early mortality during the first year of life were linked to decreased development in dive and forage ability alongside a failure to locate suitable foraging habitat.